Prenatal stress and limbic-prefrontal white matter microstructure in children aged 6–9 years: a preliminary diffusion tensor imaging study. (May 2014) - Sarkar, Sagari; Craig, Michael C.; Dell'Acqua, Flavio; O'Connor, Thomas G.; Catani, Marco; Deeley, Quinton; Glover, Vivette; Murphy, Declan G.M.
Abstract: Objectives. Maternal prenatal stress is associated with elevated risk of adverse behavioural outcomes in offspring. This association may involve developmental disruption to limbic-prefrontal white matter circuitry, of which the uncinate fasciculus is the major tract. One potential candidate for modulating brain development is maternal prenatal stress. We provide the first prospective study of prenatal stress and white matter microstructure in children. Methods. A total of 22 healthy children (mean age 7 years) of mothers recruited in pregnancy underwent diffusion tensor magnetic resonance imaging. We examined correlations between prenatal stressful life events and white matter microstructural organisation indices (fractional anisotropy (FA) and perpendicular diffusivity (Dperp )) of the uncinate fasciculus and a "control" tract. Results. Maternal prenatal stressful life events were correlated positively with right uncinate fasciculus FA, and negatively with right uncinate fasciculus Dperp in their child, with a similar trend with left uncinate fasciculus Dperp . Prenatal stress was not associated with control tract properties; sociodemographic/obstetric variables were not associated with FA/Dperp of either tract. Conclusions. Variation in maternal prenatal stress may be associated with differences in the development of white matter within brain networks underlying child social behaviour.